2020
DOI: 10.1016/j.sjbs.2020.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyphenol extract on performance, serum biochemistry, skin pigmentation and carcass characteristics in broiler chickens fed with different cereal sources under hot-humid conditions

Abstract: This study investigated the interaction between polyphenols with different cereal sources and their effects on performance, serum biochemistry, corticosterone levels and carcass characteristics in broiler chickens reared under hot-humid environment. Newly hatched coloured broiler chicks (n = 240) were randomly divided into six groups with five replicates of two different cereal sources, namely corn and broken rice-sorghum combined, and three levels of pomegranate peel polyphenol extracts (PPP) 0, 50 and 100 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…COR measured in feathers is used as a biomarker of accumulative stress ( Bortolotti et al, 2008 ), as chronic levels of COR are associated with detrimental effects on growth and related biological traits ( Scanes, 2016 ). The increase of COR with the PH diet at day 7, and the disappearance of this effect throughout the study contrasts with previous studies that reported a reduction of serum and feather COR in broilers fed with polyphenol extracts ( Gong et al, 2018 ; Gopi et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
“…COR measured in feathers is used as a biomarker of accumulative stress ( Bortolotti et al, 2008 ), as chronic levels of COR are associated with detrimental effects on growth and related biological traits ( Scanes, 2016 ). The increase of COR with the PH diet at day 7, and the disappearance of this effect throughout the study contrasts with previous studies that reported a reduction of serum and feather COR in broilers fed with polyphenol extracts ( Gong et al, 2018 ; Gopi et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, serum protein and globulin concentrations were not significantly different between treatments and were within the normal range [ 56 ]. Similarly, supplementation of broiler chickens with polyphenol extract did not affect their serum protein and globulin concentrations [ 57 ]. In addition, supplementation with CCE had no significant effects on the chemical composition (DM, CP, EE and Ash) of meat; these results are in accordance with Gopi et al [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A polyphenol extracted from grape revealed potent effects in improving serum biomarkers associated with cardiovascular disorders (Annunziata et al, 2019). Punica granatum polyphenols possess antioxidant and anti-inflammatory effects (Gopi et al, 2020). In addition, polyphenol-rich berries can decrease blood pressure and positively affect high-density lipoprotein levels (Erlund et al, 2008).…”
Section: The Biological Effects Of Polyphenolsmentioning
confidence: 99%